Development and analysis of a new integrated solar energy system with thermal storage for fresh water and power production - Demir, Murat Emre; Dincer, Ibrahim (WILEY, 2018)
In this study, a new integrated solar-energy based system for fresh water and electricity production is proposed and thermodynamically analyzed. The proposed system consists of a solar tower with a volumetric solar receiver, a Rankine cycle driven by solar power, molten salt storage subsystem and a multi-stage flash distillation (MFD) subsystem. In the present system, solar tower charges the molten salt, which flows through a heat exchanger to produce steam for the Rankine cycle. A part of the molten salt directly goes to hot storage tank after they are heated up by the solar tower. In order to keep the generated energy at the same level, molten salt in the hot storage tank compensates the deficient energy when direct normal irradiance (DNI) level is not sufficient. After the sunset, only the molten salt from the storage supplies energy to the cycle. The MFD produces the desired amount of fresh water from seawater. The seawater used for the distillation is heated by the saturated steam-water mixture coming from the steam turbine. Utilizing the output fluid as a heat source for the MFD also eliminates the external device for condensation. All system components of the integrated system are analyzed in the Engineering Equation Solver (EES). The overall energy and exergy efficiencies are calculated for each system component. The capacity of the power generation and fresh water production of the proposed system is also calculated. Moreover, a parametric study is undertaken to investigate the effects of varying ambient conditions on the system performance.
Keywords: desalination; efficiency; energy; exergy; heat storage; solar energy; MULTIOBJECTIVE OPTIMIZATION; CYCLE; Energy & Fuels; Nuclear Science & Technology